Clinical and cognitive features associated with psychosis in Parkinson's disease: a longitudinal study - Flanigan, Joseph L.; Harrison, Madaline B.; Patrie, James T.; Shah, Binit B.; Sperling, Scott A.; Wyman-Chick, Kathryn A.; Dalrymple, William Alex; Barrett, Matthew J. (Frontiers in Aging Neuroscience, 2024)
Background: Parkinson's disease psychosis (PDPsy) is associated with increased nursing home placement and mortality and is closely linked with cognitive dysfunction.Objective: Assess the clinical and cognitive features associated with PDPsy in patients without dementia.We prospectively recruited people with Parkinson's disease (PwP) without dementia for a 3-year, longitudinal study at an outpatient movement disorders clinic. Participants completed annual visits involving assessment of motor and non-motor symptoms including neuropsychological testing. PDPsy was defined as the recurring presence of visual illusions, sense of presence, hallucinations, or delusions for at least one month. Using generalized estimating equations, we conducted two sets of analyses to separately assess the clinical and the cognitive predictors of PDPsy.Results: We enrolled 105 participants. At baseline, mean age was 67.8 (SD=8.0), median disease duration was 4.9 years (IQR: 3.4-7.7), and mean MoCA was 24.8 (SD=2.3). Prevalence of PDPsy increased over three years from 31% (n=32) to 39% (n=26). Forty-five participants (43%) experienced PDPsy. Visual illusions were most common (70%, n=84), followed by hallucinations (58.3%, n=70). In multivariate analysis, of the clinical variables, only depressive symptoms (OR 1.09, 95% CI: [1.03, 1.16], p=.004) increased the odds of PDPsy; of the cognitive variables, only Trail Making Test B-A scores (OR 1.43, 95% CI: [1.06, 1.93], p=.018) significantly increased the odds of PDPsy. Conclusions: In PwP without dementia, depressive symptoms were associated with increased risk of PDPsy. Executive/attentional dysfunction was also associated with PDPsy and may mark the transition from isolated minor hallucinations to more complex psychotic symptoms.